Regional innovation idealism to prevent LBW and stunting through sacred moringa leaf innovation Creation of eating moringa leaves every sunday Enrekeng Village Soppeng District - Kartika, Ray Septianis; Suhendra, Adi; Suhandojo, Suhandojo; Rosidah, Rosidah; Robby, Uchaimid Biridloi (International Journal of Innovative Research and Scientific Studies, 2025)
Handling stunting is a regional development target in improving the level of public health. The war against stunting has been carried out by Enrekeng Village through the sacred innovation of moringa. This innovation can reduce the village to a 0% zone in 2022 free from LBW with a birth rate of 14 children. The purpose of this study is to show that the use of Moringa leaves can reduce stunting rates by using regional innovation idealism. The research method uses a case study whose justification is that the sacred moringa innovation is the only innovation to handle stunting in Soppeng district. Analyze the data using the triangulation method with the scamper model. The results of the study state that innovation idealism lies in subjective idealism, objective idealism and personal idealism. Subjective idealism is in line with the characteristics of innovation, namely complexity and observability.Objective Idealism embodies the characteristics of innovation with relative superiority. Personal idealism intersects with compatibility and testability. The meaning is that the idealism of regional innovation cannot be avoided and is the hope of everyone to realize the sustainability and benefits of maternal and child health as a whole.